Symposium 5: Athenian Democracy & Networked Learning Communities - Themelis, Chrysoula; Parchoma, Gale; Reynolds, Michael (Proceedings of the International Conference on Networked Learning, 2010)
The Athenian democracy is worthy of study if for no other reason than that it was inspiration for many academic fields. This project highlights some institutions and policies of the Athenian democracy, during its flowering in the fifth and fourth centuries BC, in order to interpret them for the benefits of networked learning communities. Concepts such as ephebes and the power of reward can be applied to both the ancient and digital era, without implying an exact parallel. New members (ephebes) need training to create their e-portfolios, acquire digital literacy and epistemic fluency to be eligible to contribute to and benefit from community management. Discussion forums could be an arena for dialogue and information exchange. Allocating labor, e-community managers could fulfill the potential of technology-enhanced learning and tutors would able to select and distribute resources that could be useful and applicable. Praxis and democratic ideals are mirrored in the framework of an economy of knowledge. Epistemologically speaking, an economy of knowledge can be seen as a theory for acquiring the full benefits and costs of coming to know and use knowledge. This theory of knowledge could be a core concept in network learning. This theory does not presume full knowledge, but it does presume democratic social construction of knowledge. On ontological grounds, subjectivity implies that there are always some alternative constructions available to choose from in dealing with the world. The reliability of democracy increases as different points of views transformed into a socially ‘agreed’ way of interaction and participation. The dark side of democracy more closely related to NL communities could shade mainly the ideas of irrational decision, monoculture (single, homogeneous culture without diversity) and demagogy. To illuminate dark corners of democratic e-communities, a form of ‘aristocratic democracy’ is used as a metaphor for the social regime. The term, aristocracy, in the Greek sense of the word, means that the best rules in every domain. To top it all, cultural pluralism could light democratic e-communities, with creativity or conflict that can promote critical thinking and dialogue.Praxis and further research are required to test the validity of the theory presented.